2012
DOI: 10.1016/j.ajpath.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Subunit c-Rel Stimulates Cardiac Hypertrophy and Fibrosis

Abstract: Cardiac remodeling and hypertrophy are the pathological consequences of cardiovascular disease and are correlated with its associated mortality. Activity of the transcription factor NF-κB is increased in the diseased heart; however, our present understanding of how the individual subunits contribute to cardiovascular disease is limited. We assign a new role for the c-Rel subunit as a stimulator of cardiac hypertrophy and fibrosis. We discovered that c-Rel-deficient mice have smaller hearts at birth, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…It is believed that the sustained overactivation of NF-κB plays an important role in the pathogenesis of hypertrophic cardiomyopathy. Studies have shown that PPARα agonists can inhibit the myocardial remodeling induced by pressure overload and improve myocardial systolic function in rats 35, 36. PPARα also plays a significant role in the regulation of neuroinflammation in numerous CNS diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the sustained overactivation of NF-κB plays an important role in the pathogenesis of hypertrophic cardiomyopathy. Studies have shown that PPARα agonists can inhibit the myocardial remodeling induced by pressure overload and improve myocardial systolic function in rats 35, 36. PPARα also plays a significant role in the regulation of neuroinflammation in numerous CNS diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that anti-inflammatory therapy may be a promising strategy against cardiac fibrosis [35]. NF-κB is a pleiotropic transcription factor that, in addition to playing fundamental roles in immunity, also regulates the expression of genes that contribute to various cardiac diseases including cardiac fibrosis [36]. Cardiac tissue consists mainly of cardiomyoctyes, which are surrounded by extracellular matrix [37].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed in SYBR Green Master Mix (Qiagen, Germantown, Maryland) with an Applied Biosystems Prism 7500 PCR system and analyzed with the SDS software as described (Keenen et al, 2010). Primer sequences for ANP and BNP were as follows: ANP 5′-ACCTGGAGGAGAAGATGCCG-3′; 5′-TGTTGCAGCCTAGTCCGCTC-3′ and BNP 5′-GTGCTGCCCCAGATGATT-3′ 5′-GGTCTATCTTCTGCCCAAAG-3′(Gaspar-Pereira et al, 2012). Primer sequences for the control 18S rRNA were 5′-AGTCCCTGCCCTTTGTACACA-3′ and 5′-GATCCGAGGGCCTCACTAAAC-3′.…”
Section: Methodsmentioning
confidence: 99%